2019
DOI: 10.1101/643569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signatures of selection in a recent invasion reveals adaptive divergence in a highly vagile invasive species

Abstract: A detailed understanding of population genetics in non-native populations helps us to identify drivers of successful introductions. However, separating adaptive change from local signatures of founding populations represents a conceptual and technical difficulty when dealing with invasive populations. The history of introductions, as well as the process of range expansion, can confound interpretation of putative adaption in response to a novel environment. Here, we investigate putative signals of selection in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 83 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…First, previous studies of starlings in Australia, South Africa, and the UK used mitochondrial control region sequence data, so the comparative strength of our study is predicated on using the same marker. Second, Australian studies that have compared population structure using mitochondrial sequence data to that of microsatellite (Rollins et al., 2011) and single nucleotide polymorphism data (Cardilini et al, 2020) found similar patterns, supporting the validity of our approach. Third, mitochondrial DNA is still one of the most reliable sources of DNA that can be extracted from historical museum specimens (Guschanski et al., 2013; Mason, Li, Helgen, & Murphy, 2011; Ramakrishnan & Hadly, 2009), and population analyses using historical specimens rely on comparable datasets from modern birds, such as this.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…First, previous studies of starlings in Australia, South Africa, and the UK used mitochondrial control region sequence data, so the comparative strength of our study is predicated on using the same marker. Second, Australian studies that have compared population structure using mitochondrial sequence data to that of microsatellite (Rollins et al., 2011) and single nucleotide polymorphism data (Cardilini et al, 2020) found similar patterns, supporting the validity of our approach. Third, mitochondrial DNA is still one of the most reliable sources of DNA that can be extracted from historical museum specimens (Guschanski et al., 2013; Mason, Li, Helgen, & Murphy, 2011; Ramakrishnan & Hadly, 2009), and population analyses using historical specimens rely on comparable datasets from modern birds, such as this.…”
Section: Introductionsupporting
confidence: 66%
“…The haplotype network including all populations (Figure 2 (Rollins et al, 2009(Rollins et al, , 2011 and evidence of local adaptation to the Australian environment has been described (Cardilini, Buchanan, Sherman, Cassey, & Symonds, 2016;Cardilini et al, 2020). However, in South Africa, no evidence of population structure was found (Berthouly-Salazar et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, starlings at the expansion front may have rapidly adapted during the Australian invasion (Rollins et al, 2016): the proportion of adult starlings in Western Australia carrying a novel mitochondrial haplotype has increased rapidly only at this range edge. A genotyping-by-sequencing survey employing a much greater number of SNP markers indicates three population subdivisions in Australia, where geographic distance explains genetic differentiation in starlings better than does environmental variation (Cardilini et al , 2020). Global F ST across all Australian populations is an order of magnitude higher than the equivalent F ST index across North America, despite similar areas sampled.…”
Section: Discussionmentioning
confidence: 94%
“…A similar project on starlings in the Australian invasion-which colonized that continent nearly concurrently with the North American invasion-found that geographic but not environmental distance explains genetic patterns there (Cardilini et al, 2020). Starlings in the Australian range show substantial population structuring and significant patterns of isolation-by-distance.…”
Section: Discussionmentioning
confidence: 97%